Membranes with cross-linked block copolymers and methods of making same
By crosslinking the total molecular weight of the block copolymer, the problem of insufficient solvent resistance and drying stability in the photolithography solvent is solved, and higher stability and solvent resistance are achieved.
Patent Information
- Application Number
- CN202380050861.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-16
- Filing Date
- 2023-06-15
- Publication Date
- 2025-02-28
AI Technical Summary
When the existing block copolymer filter membranes come into contact with the photolithography solvent, the pore structure is prone to collapse and the polymer is soluble, resulting in insufficient solvent resistance and drying stability.
The total molecular weight of the block copolymer is increased by crosslinking reaction, and the solvent resistance and drying stability of the membrane are improved. A specific method includes cross-linking reaction using a block copolymer having a carbon-carbon double bond, or a monomer substance containing an anthracene moiety for dimerization.
The crosslinked block copolymer film had a bubble point change of less than 20% when exposed to the photolithography solvent for 24 hours, indicating that it had higher stability and solvent resistance while exhibiting improved performance in tensile tests.
Smart Images

Figure CN119546382A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to filtration membranes comprising certain block copolymers. Background Art
[0002] Filter products are essential tools for modern industry, and are used to remove unwanted substances from useful fluid streams. Useful fluids treated with filters include water, liquid industrial solvents and process fluids, industrial gases for manufacturing or processing (e.g., in semiconductor manufacturing), and liquids with medical or pharmaceutical uses. Unwanted substances removed from fluids include impurities and contaminants, such as particles, microorganisms, and dissolved chemical species. Specific examples of filter applications include its use in semiconductor and microelectronic device manufacturing together with liquid materials.
[0003] In order to bring into play the filtering function, the filter may include a filter membrane, which is responsible for removing unwanted substances from the fluid passing through the filter membrane. Optionally, the filter membrane may be in the form of a flat sheet, which may be wound (e.g., in a spiral manner), flat, pleated or disc-shaped. The filter membrane may alternatively be in the form of a hollow fiber. The filter membrane may be contained in a housing or otherwise supported so that the filtered fluid enters via the filter inlet and needs to pass through the filter membrane before passing through the filter outlet.
[0004] The filter membrane can be composed of a porous structure having an average pore size that can be selected based on the purpose of the filter, that is, the type of filtration performed by the filter. Typical pore sizes are in the micron or submicron range, for example, from about 0.001 micron to about 10 microns. Sometimes membranes with an average pore size of about 0.001 to about 0.05 microns are classified as ultrafiltration membranes. Sometimes membranes with a pore size between about 0.05 and 10 microns are referred to as microporous membranes.
[0005] Filter membranes having pore sizes in the micron or submicron range can effectively remove unwanted substances from a fluid stream by either a sieving mechanism or a non-sieving mechanism, or by both. A sieving mechanism is a mode of filtration in which particles are removed from a liquid stream by mechanically retaining the particles on the surface of a filter membrane, which serves to mechanically interfere with the movement of the particles and retain the particles within the filter, mechanically preventing the flow of particles through the filter. Typically, the particles will be larger than the pores of the filter. A "non-sieving" filtration mechanism is a mode of filtration in which a filter membrane retains suspended particles or dissolved substances contained in a fluid stream passing through the filter membrane in a manner that is not merely mechanical (e.g., including an electrostatic mechanism, by which the particles or dissolved impurities are electrostatically attracted and retained on the filter surface and removed from the fluid stream; the particles may be dissolved, or may be solids having a particle size smaller than the pores of the filter medium.
[0006] Block copolymer self-assembly is a unique membrane formation technology that can precisely control pore size and pore size distribution. Polymer design is critical and requires careful consideration when designing macromolecules that microphase separate into periodic ordered structures. One such polymer is poly(isoprene-b-styrene-b-4-vinylpyridine), which is currently used to prepare filtration membranes for the life science and ultrapure water markets. However, such polymers are not fully suitable for use with many common solvents (e.g., photolithography solvents) because the pore structure tends to collapse after drying and / or the polymer is soluble in the photolithography solvent. Therefore, a filtration membrane that would be compatible with such common solvents comprising a block copolymer and such a highly ordered pore structure would be highly desirable. Summary of the invention
[0007] In general, the present disclosure provides certain block copolymer membranes suitable for use as components of filters for liquid purification and / or filtration. The block copolymers of the present disclosure undergo a crosslinking reaction to increase the total molecular weight, and are therefore believed to impart improved solvent resistance properties to the membranes, making such membranes suitable for use with solvents such as photolithography solvents. In addition, it is believed that this crosslinking treatment improves the integrity of the pore structure of the membrane during the drying step. BRIEF DESCRIPTION OF THE DRAWINGS
[0008] Figure 1 (which is a schematic diagram and not necessarily to scale) shows an example of a filter product as described herein. DETAILED DESCRIPTION
[0009] As used in this specification and the appended claims, the singular forms "a," "an," and "the" include plural referents unless the context clearly dictates otherwise. As used in this specification and the appended claims, the term "or" is generally used in its sense including "and / or" unless the context clearly dictates otherwise.
[0010] The term "about" generally refers to a range of values that are considered equivalent to the recited value (eg, having the same function or result). In many cases, the term "about" can include values that are rounded to the nearest significant figure.
[0011] The recitation of numerical ranges using endpoints includes all numbers subsumed within that range (eg, 1 to 5 includes 1, 1.5, 2, 2.75, 3, 3.80, 4, and 5).
[0012] In a first aspect, the present disclosure provides a film comprising a crosslinked block copolymer, wherein the bubble point of the film exhibits less than about 20% change when exposed to one or more photolithographic solvents for a period of 24 hours. As will be described more fully below, the crosslinked block copolymer film can be prepared from a block copolymer having carbon-carbon double bonds that can be used for crosslinking reactions as a starting material, or having an anthracene portion that can undergo a dimerization reaction. Therefore, the crosslinked block copolymer film of the present disclosure is suitable for use as a filter membrane for various fluids, and is believed to have higher stability to organic solvents and higher drying stability when compared to non-crosslinked films.
[0013] It is believed that the films of the present disclosure have drying stability, which alleviates substantially all necessity of using humectants (e.g., glycerol), which are commonly used in conventional films to maintain pore structure during manufacture and drying. Therefore, in another embodiment, the present disclosure provides films of the present disclosure, wherein the crosslinked block copolymer contains less than about 10 wt %, less than about 5 wt %, or less than about 1 wt % humectant. In this regard, the presence of such humectants in a given film can be detected by extracting the humectant from the film and analyzing it by NMR and / or IR spectroscopic analysis to determine the amount of humectant present (if present).
[0014] In addition to having greater stability in the presence of organic solvents (e.g., photolithographic solvents), the films of the present disclosure are believed to exhibit improved performance when subjected to tensile testing (e.g., tensile testing covered in ASTM method D638-14). Due to the additional mass of the crosslinked block copolymer film, we believe the film will exhibit a tensile strain at break of greater than about 5% as determined by ASTM method D638-14.
[0015] If the crosslinked block copolymer membrane has sufficient mechanical stability, it can be used directly as a component in a filtration device. Alternatively, in another aspect of the present disclosure, the block copolymer membrane can be cast on a porous substrate or base to form a composite membrane, and then subjected to a crosslinking reaction. Therefore, in another aspect, the present disclosure provides a method for preparing a composite membrane, comprising:
[0016] a. a porous substrate; and
[0017] b. a crosslinked block copolymer thin film layer; wherein the bubble point of the film exhibits less than about 20% change when exposed to one or more photolithographic solvents for a period of 24 hours;
[0018] The method includes casting a block copolymer having residual carbon-carbon double bonds or anthracene moieties onto a porous substrate and subjecting the block copolymer membrane layer to a cross-linking reaction.
[0019] Casting of the crosslinked block copolymer membrane layer onto a porous substrate can be achieved using known methods. See, for example, "Tuning Structure and Properties of Graded Triblock Terpolymer-Based Mesoporous and Hybrid Films", WA Phillip et al., Nano Express ( Nano Lett. ) 2011, 11, 2892-2900, which describes a method for forming a block copolymer membrane by using a combination of controlled solvent evaporation and nonsolvent-induced phase separation (NIPS). In general, we can use the method described in the cited reference to cast the membrane onto a glass surface and replace its porous substrate, thereby forming a composite membrane comprising a porous substrate and a crosslinked block copolymer layer, which can then be subjected to a crosslinking reaction to obtain the membrane of the present disclosure.
[0020] Thus, in another aspect, the present disclosure provides a composite membrane comprising a porous base layer and a crosslinked block copolymer layer, wherein the membrane exhibits less than about 20% change in bubble point when exposed to one or more photolithographic solvents for a period of 24 hours.
[0021] The porous substrate layer may be composed of any conventional natural or synthetic porous material (e.g., a non-woven fiber material or a porous polymeric membrane). Exemplary polymers in this context include polyolefins and halogenated polymers. Exemplary polyolefins include polyethylene, polypropylene, polymethylpentene, polybutylene, polyisobutylene, and copolymers of two or more of ethylene, propylene, and butylene. In another specific embodiment, the porous substrate material comprises ultra-high molecular weight polyethylene (UPE). UPE filter materials (e.g., UPE membranes) are typically composed of a molecular weight (viscosity average molecular weight) greater than about 1×10 6 Dalton (Da) (e.g., about 1×10 6 -9×10 6 Da or 1.5×10 6 -9×10 6Da range). In this porous polymer base support or substrate layer, crosslinking between polyolefin polymers (e.g., polyethylene) can be promoted by using heat or crosslinking chemicals, such as peroxides (e.g., dicumyl peroxide or di-tert-butyl peroxide), silanes (e.g., trimethoxyvinylsilane), or azo ester compounds (e.g., 2,2'-azo-bis(2-acetoxy-propane). Exemplary halogenated polymers include polytetrafluoroethylene (PTFE), polychlorotrifluoroethylene (PCTFE), fluorinated ethylene polymers (FEP), polyhexafluoropropylene, and polyvinylidene fluoride (PVDF).
[0022] Additionally, the porous substrate layer may be composed of a polymer selected from the group consisting of polyimide, polysulfone, polyether-sulfone, polyarylsulfone polyamide, polyacrylate, polyester, polyamide-imide, cellulose, cellulose ester, polycarbonate, or a combination thereof.
[0023] As noted above, the membranes of the present disclosure can be prepared via a variety of alternative crosslinking reactions. Therefore, in another aspect, the present disclosure provides a method for preparing a crosslinked block copolymer membrane, the method comprising treating a block copolymer membrane having residual carbon-carbon double bonds to form a crosslinked block copolymer, wherein the treatment is selected from the group consisting of:
[0024] a. treating with a sulfur compound at a temperature sufficient to induce crosslinking;
[0025] b. treating with a thermal free radical initiator at a temperature sufficient to induce crosslinking;
[0026] c. treating with ultraviolet light in the presence of a free radical photoinitiator; and
[0027] d. Treatment with electron beam radiation.
[0028] In option a. above, treatment with a sulfur compound (e.g., polymeric sulfur) at a temperature sufficient to induce crosslinking refers to conventional methods of vulcanization of natural and synthetic rubbers as is well understood. See, e.g., U.S. Pat. Nos. 2,560,045, 4,238,470, 7,569,639, RE 25007E, 10,125,239, and 10,011,663, which are incorporated herein by reference in their entirety.
[0029] In option b., treatment with a thermal free radical initiator refers to the use of a thermally activated free radical initiator, such as benzoyl peroxide or azobisisobutyronitrile (AIBN), each of which decomposes at elevated temperatures to provide a free radical flux, thereby enabling crosslinking reactions between carbon-carbon double bond moieties present within the polymer matrix. The block copolymer starting material can be converted into a filtration membrane and then treated, for example, with a solvent solution containing a thermally activated free radical initiator and then heated.
[0030] In option c., treatment with a photoradical initiator can be carried out in a similar manner by exposing the block copolymer film having residual carbon-carbon double bonds to a free radical initiator (e.g. This is accomplished with a solution of 2595 (Ciba) (2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone), benzophenone or ammonium persulfate. The block copolymer starting material can be converted into a filtration membrane and then treated, for example, with a solvent solution containing a photoactivated free radical initiator and then heated.
[0031] In option d., the block copolymer film with residual carbon-carbon double bonds can be exposed to electron beam radiation in the absence of an initiator to promote crosslinking. See, e.g., "Effect of Electron Beam Radiation on Tensile and Viscoelastic Properties of Styrenic Block Copolymers", J. Wu et al., Polymer Engineering and Science ( Polym.Eng.Sci. ), 54:2979-2988, 2014. In this regard, dose levels in the range of 40-240 kGy may be used, and the dose level may be adjusted to the desired level of crosslink density and proportion of available carbon-carbon double bonds present within the polymer matrix.
[0032] Alternatively, in one embodiment of the present disclosure, the block copolymer used to form the filter membrane is designed such that at least a portion of its composition contains the residue of a monomeric substance containing an anthracene moiety. Such polymers containing these anthracene moieties can be effectively crosslinked by subjecting the resulting block copolymer to ultraviolet light, which achieves a dimerization reaction between the anthracene moieties present in the polymeric matrix. Therefore, in another aspect, the present disclosure provides a method for preparing a crosslinked block copolymer film, wherein the film comprises at least one block copolymer comprising anthracene residues, the method comprising exposing the block copolymer comprising anthracene residues to ultraviolet light.
[0033] In this way, it is believed that the method as described above is applicable to realize the cross-linking reaction between at least a portion of the residual carbon-carbon double bonds present in the block copolymer matrix. It is believed that this cross-linking reaction must produce a higher molecular weight polymer and a polymer that exhibits improved resistance to those solvents used in, for example, photolithography. In this regard, exemplary photolithography solvents include n-butyl acetate, isopropyl alcohol, 2-ethoxyethyl acetate, xylene, cyclohexanone, ethyl acetate, isopentyl ether, methyl-2-hydroxyisobutyrate, methyl isobutyl carbinol, methyl isobutyl ketone, isopentyl acetate, undecane, propylene glycol methyl ether, propylene glycol monomethyl ether acetate, and a mixed solution (surface tension of 27.7 mN / m) of a mixing ratio of propylene glycol monomethyl ether and propylene glycol monomethyl ether acetate (7:3). Additional solvents that are believed to be capable of being purified using the membranes of the present disclosure include ethanol, methanol, butanol, hexanol, heptanol, octanol, decanol, benzyl alcohol; amides such as N,N-dimethylacetamide, N,N-dimethylformamide, N-methyl-2-pyrrolidone, piperidine, morpholine, pyridine, diethylenetriamine, pyrrolidone, methoxyethane, tetrahydrofuran, dioxane, dimethoxyethane; esters such as n-butyl acetate, methyl acetate, ethyl acetate, propyl acetate, pentyl acetate, amyl acetate, butyl ... acetate), methyl formate, ethyl formate, propyl formate, butyl formate, ethyl lactate, propyl lactate, ethylene glycol, propylene glycol, triethylene glycol, ethylene glycol monomethyl ether, propylene glycol monomethyl ether, triethylene glycol monomethyl ether, chloroform, hexane, decane, octane, cyclohexane, pentane, toluene, xylene, benzene, methyl ethyl ketone, octanone, nonanone, acetone, heptanone, hexanone, diisobutyl ketone, phenylacetone, cyclohexanone, acetylacetone, propylene carbonate, acetonitrile, sulfolane and dimethyl sulfoxide, and mixtures thereof, and mixtures with water.
[0034] As used herein, the term "block copolymer" refers to the simplest block copolymer comprising two or more linear segments or "blocks", wherein adjacent segments include different constituent units, wherein only one constituent unit is in each block. However, this simple architecture is not the only architecture that can cause self-assembly at nano and intermediate scales. Such architectures, which will be referred to as composite blocks or copolymer architectures, may include, for example, intermediate non-repeating units between different end groups of the block (joining block) and the chain end. There are even more complex block architectures and block copolymer architectures, wherein at least a portion of a block or at least a portion of a joining block or one or more end groups include a more complex structure or composition than a linear single constituent unit chain. Such complex architectures include, but are not limited to, periodic or random mixtures of different constituent units in one or more blocks, graft copolymer blocks, ring blocks or block copolymers, gradient blocks or crosslinked blocks. It is suitable to allow the incompatible segments of the block copolymer to separate (self-assemble) into different domains and to process using the disclosed method to produce any block copolymer architecture / topology of a porous block copolymer material.
[0035] Some examples of suitable block chemistries include, but are not limited to: poly(isobutylene), poly(isoprene), poly(butadiene), poly(propylene glycol), poly(ethylene oxide), poly(dimethylsiloxane), poly(ether sulfone), poly(sulfone), poly(hydroxystyrene), poly(methylstyrene), poly(ethylene glycol), poly(2-hydroxyethyl methacrylate), poly(acrylamide), poly(N,N-dimethylacrylamide), poly(propylene oxide), poly(styrene sulfonate), poly(styrene), poly(ethylene), poly(vinyl chloride), poly(2-(perfluorohexyl)ethyl methacrylate), poly(tetrafluoroethylene), poly(vinylidene fluoride), poly(pentafluorostyrene), poly(acrylic acid), poly(2-vinylpyridine) , poly(4-vinylpyridine), poly(3-vinylpyridine), poly(N-isopropylacrylamide), poly(dimethylaminoethyl methacrylate), poly(glycidyl methacrylate), poly(ethyleneimine), poly(lactic acid), poly(acrylonitrile), poly(methyl acrylate), poly(butyl methacrylate), poly(methyl methacrylate), poly(n-butyl acrylate), poly(acylamino acid), poly(isocyanate), poly(ethyl cyanoacrylate), poly(allylamine hydrochloride), or a substituted equivalent of any of the foregoing, provided that the block copolymer as a whole has at least some carbon-carbon double bond moieties available for crosslinking reactions within the polymer matrix, or has anthracene moieties capable of dimerization reactions as described above.
[0036] Block copolymer starting materials suitable for making the membranes of the present disclosure include M n About 1×10 3 About 1×10 7g / mol, and includes diblock, triblock, higher order BCPs (i.e., tetrablock, pentablock, etc.). The polydispersity index (PDI) of a block copolymer is a measure of the heterogeneity of molecular size and shows the distribution of molar mass in a sample of BCPs. It is the average molar mass (M w ) and number average molar mass (M n At least one embodiment of the BCP as contemplated herein has a PDI in the range of about 1.0 to about 3.0.
[0037] Exemplary block copolymers suitable for use as starting materials in the present disclosure can be found in U.S. Pat. Nos. 10,711,111 and 9,527,041; and U.S. Patent Publication Nos. 2021 / 0040281, 2021 / 0370237, and 2009 / 0173694, the disclosures of which are incorporated herein by reference in their entireties.
[0038] One specific block copolymer starting material is a polymer known as poly(1,4-isoprene)-b-poly(styrene)-b-poly(vinylpyridine), which is commercially available from Polymer Source, Inc. of Quebec, Canada.
[0039]
[0040] In such structures, residual carbon-carbon double bonds from the polymerization of isoprene monomers provide platforms for cross-linking reactions.
[0041] Block copolymers suitable for use in the present disclosure can advantageously self-assemble into nanoscale structures and form micelles of uniform size in the casting solution, which in turn provide a highly ordered isoporous structure on the membrane surface. See, e.g., U.S. Patent Publication No. 2014 / 0217012 (incorporated herein by reference), which describes the manufacture of filtration membranes via a combination of controlled solvent evaporation and wet precipitation methods known as self-assembly and non-solvent induced phase separation (SNIPS).
[0042] In addition, the membrane starting material can be prepared by the method described in U.S. Patent Publication No. 2021 / 0040281, which is incorporated herein by reference in its entirety. In the cited method, the formation of the block copolymer membrane includes the following steps: (a) preparing a polymer solution by mixing at least one block copolymer, wherein the at least one block copolymer is combined with at least one solvent; (b) extruding the polymer solution into a membrane on a non-porous substrate; (c) evaporating at least a portion of at least one chemical in the polymer solution; and (d) immersing the membrane in a coagulation bath.
[0043] Alternatively, in the cited method for forming a block copolymer (either stand-alone or as part of a composite), the membrane also includes the steps of: (a) formulating a polymer solution by mixing at least one block copolymer, wherein the at least one block copolymer is combined with at least one solvent; (b) extruding the polymer solution into a membrane on a non-porous substrate; (c) evaporating at least a portion of at least one chemical in the polymer solution; (d) immersing the membrane in a coagulation bath; and (e) rinsing the block copolymer membrane.
[0044] If the underlying film is sufficiently stable, the crosslinking reaction of the present disclosure can be performed after the drying step; if it is not stable, the crosslinking reaction can be performed on the film before drying. Therefore, once dried, the crosslinked film substantially retains its pore structure. In this regard, it is believed that this crosslinking method will provide a film whose bubble point exhibits less than about 20% change, less than about 15% change, or less than about 10% change when exposed to one or more photolithographic solvents for a period of 24 hours. In addition, it is believed that the crosslinked film also exhibits improved acid / base stability. By the bubble point test method, a sample of a porous polymeric filter membrane is immersed in a liquid with a known surface tension and wetted with it, and a gas pressure is applied to one side of the sample. The gas pressure is gradually increased. The minimum pressure at which the gas flows through the sample is called the bubble point. In order to determine the bubble point of a porous material, a sample of the porous material is immersed in ethoxy-nonafluorobutane HFE 7200 (available from 3M) and wetted with it at a temperature of 20-25°C (e.g., 22°C). Gas pressure is applied to one side of the sample using compressed air and the gas pressure is gradually increased. The minimum pressure at which the gas flows through the sample is called the bubble point.
[0045] Once manufactured, the starting material membrane may be subjected to one or more of the above-mentioned techniques in order to achieve the desired degree of cross-linking density within the polymer matrix. Subsequently, the membrane may then be dried and fabricated into the desired filtration structure.
[0046] The filter membrane as disclosed herein may be contained within a larger filter structure (e.g., a multi-layer filter assembly or a filter cartridge) used in a filter system. The filter system will place the filter membrane, for example, as part of a multi-layer filter assembly or as part of a filter cartridge, in a filter housing to expose the filter membrane to the flow path of the liquid chemical to cause at least a portion of the liquid chemical to flow through the filter membrane so that the filter membrane removes an amount of impurities or contaminants from the liquid chemical. The structure of the multi-layer filter assembly or filter cartridge may include one or more of the following: various additional materials and structures that support the composite filter membrane within the filter assembly or filter cartridge column to cause the fluid to flow from the filter inlet through the composite membrane (including the filter layer) and through the filter outlet, thereby passing through the composite filter membrane when passing through the filter. The filter membrane supported by the filter assembly or filter cartridge column can be in any suitable shape, such as a pleated cylinder, a cylindrical pad, one or more non-pleated (flat) cylindrical sheets, pleated sheets.
[0047] One example of a filtration structure including a filter membrane in the form of a pleated cylinder can be prepared to include the following component parts, any of which can be included in the filter construction but may not be required: a rigid or semi-rigid core that supports the pleated cylindrical coated filter membrane at its interior opening; a rigid or semi-rigid cage that supports or surrounds the exterior of the pleated cylindrical coated filter membrane outside the filter membrane; optional end pieces or "pucks" located at each of the two opposite ends of the pleated cylindrical coated filter membrane; and a filter housing that includes an inlet and an outlet. The filter housing can have any suitable and desired size, shape, and material, and preferably can be made of a suitable polymeric material.
[0048] As an example, Figure 1 A filter assembly 30 is shown, which is a product having a pleated cylindrical assembly 10 and an end piece 22 and other optional components. The cylindrical assembly 10 includes a filter membrane 12 as described herein and is pleated. The end piece 22 is attached to one end (e.g., "potted") of the cylindrical filter assembly 10. The end piece 22 may preferably be made of a melt-processable polymeric material. A core (not shown) may be located at the interior opening 24 of the pleated cylindrical assembly 10, and a cage (not shown) may be placed on the outside surrounding the pleated cylindrical assembly 10. A second end piece (not shown) may be attached to the second end ("potted") of the pleated cylindrical assembly 30. Subsequently, the resulting pleated cylindrical assembly 30 having two opposing sealed ends and an optional core and cage may be placed in a filter housing, which includes an inlet and an outlet and is configured so that all fluids entering the inlet must pass through the filter membrane 12 before leaving the filter at the outlet.
[0049] Therefore, based on the several illustrative embodiments of the present disclosure described, it will be readily understood by those skilled in the art that other embodiments may be made and used within the scope of the appended claims. The many advantages of the present disclosure covered by this document have been described in the foregoing description. However, it should be understood that the present disclosure is merely illustrative in many respects. Of course, the scope of the present disclosure is defined by the language in which the appended claims are expressed.
[0050] aspect
[0051] In a first aspect, the present disclosure provides a film comprising a crosslinked block copolymer.
[0052] In a second aspect, the present disclosure provides a film comprising a crosslinked block copolymer, wherein the film exhibits less than about 20% change in bubble point when exposed to one or more photolithographic solvents for a period of 24 hours.
[0053] In a third aspect, the present disclosure provides a film of the first or second aspect having a thickness of less than or equal to about 75 microns.
[0054] In a fourth aspect, the present disclosure provides the film of any one of the first to third aspects, wherein the copolymer is a terpolymer.
[0055] In a fifth aspect, the present disclosure provides the film of any one of the first to fourth aspects, wherein the film contains less than about 10% by weight of a humectant.
[0056] In a sixth aspect, the present disclosure provides the film of the fifth aspect, wherein the humectant is glycerin.
[0057] In a seventh aspect, the present disclosure provides the film of any one of the first to sixth aspects, wherein the film exhibits a tensile strain at break of greater than about 5% by ASTM method D638-14.
[0058] In an eighth aspect, the present disclosure provides the membrane of any one of the first to seventh aspects, wherein the cross-linked block copolymer is prepared from a block copolymer having anthracene residues.
[0059] In a ninth aspect, the present disclosure provides a composite membrane comprising a porous base layer and a cross-linked block copolymer layer.
[0060] In a tenth aspect, the present disclosure provides a composite membrane comprising a porous base layer and a crosslinked block copolymer layer, wherein the membrane exhibits less than about 20% change in bubble point when exposed to one or more photolithographic solvents for a period of 24 hours.
[0061] In an eleventh aspect, the present disclosure provides the composite membrane of the ninth or tenth aspect, wherein the porous substrate is a non-woven material.
[0062] In a twelfth aspect, the present disclosure provides the composite membrane of the ninth, tenth or eleventh aspect, wherein the porous substrate is selected from a polyolefin or a halogenated polyolefin polymer.
[0063] In a thirteenth aspect, the present disclosure provides the composite film of any one of the ninth to twelfth aspects, wherein the film has a thickness of less than about 400 microns.
[0064] In a fourteenth aspect, the present disclosure provides a composite membrane of any one of aspects nine to thirteen, wherein the porous base layer comprises a polymer selected from the group consisting of polyethylene, polypropylene, polymethylpentene, polybutylene, polyisobutylene, polymethylpentene, polybutylene, polyisobutylene; and copolymers of two or more of ethylene, propylene, and butene polyimide, polysulfone, polyether-sulfone, polyarylsulfone polyamide, polyacrylate, polyester, polyamide-imide, cellulose, cellulose ester, polycarbonate, or a combination thereof.
[0065] In a fifteenth aspect, the present disclosure provides the composite membrane of any one of the ninth to fourteenth aspects, wherein the cross-linked copolymer is prepared from a block copolymer having anthracene residues.
[0066] In a sixteenth aspect, the present disclosure provides a filter comprising the membrane of the first or second aspect.
[0067] In a seventeenth aspect, the present disclosure provides a filter comprising the composite membrane of the ninth or tenth aspect.
[0068] In an eighteenth aspect, the present disclosure provides a method for preparing a cross-linked block copolymer membrane, the method comprising treating a block copolymer membrane having residual carbon-carbon double bonds, wherein the treatment is selected from the group consisting of:
[0069] a. treating with a sulfur compound at a temperature sufficient to induce crosslinking;
[0070] b. treating with a thermal free radical initiator at a temperature sufficient to induce crosslinking;
[0071] c. treating with ultraviolet light in the presence of a free radical photoinitiator; and
[0072] d. Exposure to electron beam radiation.
[0073] In a nineteenth aspect, the present disclosure provides a method for preparing a crosslinked block copolymer film, wherein the film comprises at least one block copolymer comprising anthracene residues, comprising exposing the block copolymer comprising anthracene residues to ultraviolet light.
[0074] In a twentieth aspect, the present disclosure provides the method of the eighteenth aspect, wherein the method is option a. treating with a sulfur compound at a temperature sufficient to induce crosslinking.
[0075] In a twenty-first aspect, the present disclosure provides the method of aspect eighteen, wherein the method is option d. exposing to electron beam radiation.
[0076] In a twenty-first aspect, the present disclosure provides the method of aspect eighteen, wherein the method is option b. treating with a thermal free radical initiator.
[0077] In a twenty-second aspect, the present disclosure provides the method of aspect eighteen, wherein the method is option c. treating with a photo radical initiator, and the initiator is selected from (2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone) or ammonium persulfate.
[0078] In a twenty-third aspect, the present disclosure provides a method for preparing a composite membrane, comprising:
[0079] a. a porous substrate; and
[0080] b. a crosslinked block copolymer thin film layer; wherein the bubble point of the film exhibits less than about 20% change when exposed to one or more photolithographic solvents for a period of 24 hours;
[0081] It includes casting a block copolymer having residual carbon-carbon double bonds or anthracene moieties onto a porous substrate and subjecting the block copolymer membrane layer to a cross-linking reaction.
[0082] In a twenty-fourth aspect, the present disclosure provides a method for preparing a composite membrane, comprising:
[0083] a. a porous substrate; and
[0084] b. a crosslinked block copolymer thin film layer; wherein the bubble point of the film exhibits less than about 20% change when exposed to one or more photolithographic solvents for a period of 24 hours;
[0085] The method comprises casting a block copolymer having residual carbon-carbon double bonds onto a porous substrate to form a composite membrane, and treating the block copolymer membrane having residual carbon-carbon double bonds, wherein the treatment is selected from the group consisting of:
[0086] i. treating with a sulfur compound at a temperature sufficient to induce crosslinking;
[0087] ii. treating with a thermal free radical initiator at a temperature sufficient to induce crosslinking;
[0088] iii. treating with ultraviolet light in the presence of a free radical photoinitiator; and
[0089] iv. Exposure to electron beam radiation.
[0090] In a twenty-fifth aspect, the present disclosure provides a method for preparing the composite membrane of the twenty-fourth aspect, wherein the method is option i. treating with a sulfur compound at a temperature sufficient to induce crosslinking.
[0091] In a twenty-sixth aspect, the present disclosure provides a method for preparing the composite membrane of the twenty-fourth aspect, wherein the method is option iv. exposing to electron beam radiation.
[0092] In a twenty-seventh aspect, the present disclosure provides a method for preparing the composite membrane of the twenty-fourth aspect, wherein the method is option ii. treating with a thermal free radical initiator.
[0093] In a twenty-eighth aspect, the present disclosure provides a method for preparing the composite film of the twenty-fourth aspect, wherein the method is option iii. treating with a photoradical initiator.
[0094] In a twenty-ninth aspect, the present disclosure provides a method for preparing a composite membrane, comprising:
[0095] a. a porous substrate; and
[0096] b. a crosslinked block copolymer thin film layer; wherein the bubble point of the film exhibits less than about 20% change when exposed to one or more photolithographic solvents for a period of 24 hours;
[0097] It includes casting a block copolymer having residual anthracene moieties onto the porous substrate to form a composite membrane, and exposing the block copolymer including anthracene residues to ultraviolet light.
Claims
1. A film comprising: A crosslinked block copolymer wherein the bubble point of the film exhibits less than about 20% change when exposed to one or more photolithographic solvents for a period of 24 hours.
2. The film of claim 1, wherein the film has a thickness of less than or equal to about 75 microns thick.
3. The film of any one of the preceding claims, wherein the copolymer is a terpolymer.
4. The film of any one of the preceding claims, wherein the film contains less than about 10% by weight humectant.
5. The film of claim 4, wherein the humectant is glycerin.
6. The film of any of the preceding claims, wherein the film exhibits a tensile strain at break of greater than about 5% as measured by ASTM method D638-14.
7. The membrane according to any one of the preceding claims, wherein the crosslinked block copolymer is prepared from a block copolymer having anthracene residues.
8. The membrane according to any one of the preceding claims, wherein the membrane is a composite membrane comprising a porous base layer and the crosslinked block copolymer layer.
9. The membrane of claim 8, wherein the porous substrate is a non-woven material.
10. The membrane of claim 8, wherein the porous substrate is selected from a polyolefin or a halogenated polyolefin polymer.
11. The film of any one of claims 8 to 10, wherein the film has a thickness of less than or equal to about 400 microns.
12. The membrane of claim 8, wherein the porous substrate comprises: a polymer selected from the group consisting of polyethylene, polypropylene, polymethylpentene, polybutylene, polyisobutylene, polymethylpentene, polybutylene, polyisobutylene; and copolymers of two or more of ethylene, propylene, and butylene polyimides, polysulfones, polyether-sulfones, polyarylsulfones polyamides, polyacrylates, polyesters, polyamide-imids, cellulose, cellulose esters, polycarbonates, or combinations thereof.
13. A filter comprising a membrane according to any one of the preceding claims.
14. A method of using a membrane according to any one of claims 1 to 12 or a filter according to claim 13, the method comprising passing a photolithography solvent through the membrane.
15. The method of claim 14, wherein the photolithography solvent is selected from the group consisting of n-butyl acetate, isopropyl alcohol, 2-ethoxyethyl acetate, xylene, cyclohexanone, ethyl acetate, isoamyl ether, methyl-2-hydroxyisobutyrate, methyl isobutyl carbinol, methyl isobutyl ketone, isoamyl acetate, undecane, propylene glycol methyl ether, propylene glycol monomethyl ether acetate, and combinations thereof.
16. A method for preparing a cross-linked block copolymer membrane, the method comprising treating a block copolymer membrane having residual carbon-carbon double bonds to form a cross-linked block copolymer.
17. A method according to claim 16, wherein the treatment is with a sulfur compound at a temperature sufficient to induce crosslinking.
18. The method of claim 16, wherein the treating is with a thermal free radical initiator at a temperature sufficient to induce crosslinking.
19. The method of claim 16, wherein the treating is with ultraviolet light in the presence of a free radical photoinitiator.
20. The method of claim 16, wherein the treating is exposure to electron beam radiation.
21. A method for preparing a cross-linked block copolymer film comprising exposing a block copolymer comprising anthracene residues to ultraviolet light to form a cross-linked block copolymer film.
22. The method according to claim 21, further comprising using treatment b., and the thermal free radical initiator is benzoyl peroxide or azobisisobutyronitrile.
23. The method of claim 21 further comprising using treatment c and a free radical photoinitiator (2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone) or ammonium persulfate.
24. The method of any one of claims 16 to 23, wherein the bubble point of the film exhibits less than about 20% change when exposed to one or more photolithographic solvents for a period of 24 hours.
25. The method of any one of claims 16 to 24, wherein the membrane is a composite membrane comprising a porous base layer and the crosslinked block copolymer layer.
Citation Information
Patent Citations
Vulcanizing composition containing cyclododecasulfur and improved cyclododecasulfur compound
US10011663B2
Vulcanization composition having reduced allergenic potential, and elastomeric articles formed therewith
US10125239B2
Multiblock copolymer films, methods of making same, and uses thereof
US10711111B2
Isoporous membrane and method of production thereof
US20090173694A1
Multiblock copolymer films, methods of making same, and uses thereof
US20140217012A1